2008
DOI: 10.1007/s10265-008-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-monophyly of the woody bamboos (Bambuseae; Poaceae): a multi-gene region phylogenetic analysis of Bambusoideae s.s.

Abstract: The taxonomy of Bambusoideae is in a state of flux and phylogenetic studies are required to help resolve systematic issues. Over 60 taxa, representing all subtribes of Bambuseae and related non-bambusoid grasses were sampled. A combined analysis of five plastid DNA regions, trnL intron, trnL-F intergenic spacer, atpB-rbcL intergenic spacer, rps16 intron, and matK, was used to study the phylogenetic relationships among the bamboos in general and the woody bamboos in particular. Within the BEP clade (Bambusoidea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
117
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 35 publications
20
117
1
7
Order By: Relevance
“…Bamboo has a rather striking life history, characterized by a prolonged vegetative phase lasting decades before flowering, thereby inhibiting genetic improvement. Recent genomic studies in bamboo have included genome-wide full-length cDNA sequencing 2 , chloroplast genome sequencing 3 , identification of syntenic genes between bamboo and other grasses 4 and phylogenetic analysis of Bambusoideae subspecies 5 . Fifty-nine simple sequence repeat markers from rice and sugarcane were used in the genetic diversity analyses of 23 bamboo species 6 , and 2 species-specific sequence-characterized amplified region markers were developed in the identification of different bamboo species 7 .…”
Section: E T T E R Smentioning
confidence: 99%
“…Bamboo has a rather striking life history, characterized by a prolonged vegetative phase lasting decades before flowering, thereby inhibiting genetic improvement. Recent genomic studies in bamboo have included genome-wide full-length cDNA sequencing 2 , chloroplast genome sequencing 3 , identification of syntenic genes between bamboo and other grasses 4 and phylogenetic analysis of Bambusoideae subspecies 5 . Fifty-nine simple sequence repeat markers from rice and sugarcane were used in the genetic diversity analyses of 23 bamboo species 6 , and 2 species-specific sequence-characterized amplified region markers were developed in the identification of different bamboo species 7 .…”
Section: E T T E R Smentioning
confidence: 99%
“…The close relationships between the Arthrostylidiinae and Guaduinae as sister groups and the absence of node support for the Arthrostylidiinae subtribe has been found in previous phylogenetic analyses (Kelchner and Clark, 1997;Guala et al, 2000;Zhang and Clark, 2000;BouchenakKhelladi et al, 2008;Ruiz-Sanchez et al, 2008;Sungkaew et al, 2009). The Chusqueinae is corroborated as sister to the Arthrostylidiinae+Guaduinae clade, with good node support as in previous phylogenetic analyses (Kelchner and Clark, 1997;Ruiz-Sanchez et al, 2008;Sungkaew et al, 2009;Fisher et al, 2009).…”
Section: Discussionmentioning
confidence: 76%
“…Bouchenak-Khelladi et al (2008) found that the bamboo subfamily is monophyletic but found paraphyly in the Bambuseae (woody bamboos), while the Paleotropical and Neotropical woody bamboos are sister to the Olyreae (herbaceous bamboos), and this clade sister to temperate woody bamboos. These results were later confirmed by a multi-gene phylogeny of the Bambusoideae (Sungkaew et al, 2009). In the paraphyletic woody bamboos with nine recognized subtribes, only three subtribes, (Chusquineae, Guaduinae and Melocanniinae) have been recovered as monophyletic groups (Kelchner and Clark, 1997;Clark et al, 2007;RuizSanchez et al, 2008;Fisher et al, 2009;Sungkaew et al, 2009), and the rest of the subtribes are not monophyletic EDUARDO RUIZ-SANCHEZ groups (Guo et al, 2001(Guo et al, , 2002Guo and Li, 2004;Clark et al, 2007;Yang et al, 2008;Bouchenak-Khelladi et al, 2008;Peng et al, 2008;Sungkaew et al, 2009;Triplett and Clark, 2010).…”
mentioning
confidence: 67%
See 2 more Smart Citations